2021
DOI: 10.51698/aloma.2015.33.2.49-58
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Problematic Internet and mobile phone usage in adolescents

Abstract: This study uses an innovative statistical strategy to test the role of certain variables as predictors of problematic Internet and mobile phone usage among adolescents in Spain and in the United Kingdom . A paper-and-pencil questionnaire was used, with socio-demographics and patterns of technology usage as variables, and two tests were administered: the Problematic Internet Entertainment Use Scale for Adolescents (PIEUSA) and the Mobile Phone Problem Use Scale for Adolescents (MPPUSA). The overall sample size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…On the other hand, and responding to RQ2, we can see that women tend to use their smartphones for longer periods of time, which is one of the risk factors for PSU. Moreover, they show a higher PSU, which is consistent with numerous investigations [25,[38][39][40][41][43][44][45]. As indicated by different authors [46,47], women's smartphone use is predominantly social (e.g., social networking or instant messaging), compared to a more diverse pattern for men.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…On the other hand, and responding to RQ2, we can see that women tend to use their smartphones for longer periods of time, which is one of the risk factors for PSU. Moreover, they show a higher PSU, which is consistent with numerous investigations [25,[38][39][40][41][43][44][45]. As indicated by different authors [46,47], women's smartphone use is predominantly social (e.g., social networking or instant messaging), compared to a more diverse pattern for men.…”
Section: Discussionsupporting
confidence: 87%
“…It is worth noting the difficulty in assessing and comparing the prevalence of PSU due to the inconsistency of diagnostic criteria and assessment methods [36]. Additionally, although some studies have found no sex differences [37], there is some consensus in the scientific evidence that women are at higher risk of developing PSU [38][39][40][41][42][43][44][45]. These differences could be caused by a different pattern of smartphone use, with women using smartphones for social purposes (i.e., social networking or instant messaging) and men for more varied purposes, such as video games, calls, and multimedia content [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported a significant positive association between girls and problematic mobile device usage [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Contrasting this, several studies documented a significant positive association between boys and problematic mobile device usage [ 56 ] or revealed higher scores in boys than in girls [ 32 , 44 , 45 , 57 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The parent’s educational level significantly contributes to problematic mobile device use as reported in [ 53 , 58 , 61 , 62 ]. Parents with lower educational levels tend to allow their children to spend extra time on a mobile device compared to parents with higher educational levels [ 22 , 62 , 63 , 64 , 65 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%